1994
DOI: 10.1002/jcb.240560412
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hsp47, Grp78, and Grp94 with procollagen supports the successive or coupled action of molecular chaperones

Abstract: Hsp47, Grp78, and Grp94 have been implicated with procollagen maturation events. In particular, Hsp47 has been shown to nascent procollagen alpha 1(I) chains in the course of synthesis and/or translocation into the endoplasmic reticulum (ER). Although, Hsp47 binding to gelatin and collagen has previously been suggested to be independent of ATP. Grp78 and Grp94 are known to dissociate from its substrates by an ATP-dependent release mechanism. The early association of Hsp47 with procollagen and its relatively la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 32 publications
1
54
0
1
Order By: Relevance
“…These include its specificity for procollagens as well as an atypical binding profile whereby it interacts with both folded and unfolded conformations of its target protein (11,13,14,16). The results of the current study indicate that Hsp47 can act as a primary stimulator of type I collagen production.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These include its specificity for procollagens as well as an atypical binding profile whereby it interacts with both folded and unfolded conformations of its target protein (11,13,14,16). The results of the current study indicate that Hsp47 can act as a primary stimulator of type I collagen production.…”
Section: Discussionmentioning
confidence: 72%
“…Hsp47 is expressed only by collagen-producing cells (8,9) and in vitro binds to collagens type I to V as well as gelatin (10). Within the ER, Hsp47 has been found to interact with nascent type I procollagen chains (11,12), with fully translated pro␣ collagen chains (13), with non-helical and poorly hydroxylated procollagen trimers (14) and with well-hydroxylated, triple helical procollagen (15,16). Once the procollagen-Hsp47 complex reaches the cis-Golgi, Hsp47 dissociates and is recycled back to the ER (13,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Collagen I is one of the most abundantly secreted proteins in the synthetic phenotype hVSMCs, and the modification of procollagen I in the ER and Golgi apparatus is essential for the maturation of collagen I. [19][20][21] Thus, we examined the effects of Gipie knockdown on the maturation of collagen I in hVSMCs to elucidate the participation of Gipie in the ER function under mild or physiological ER stress. A Western blot analysis showed that knockdown of Gipie decreased the production of the mature forms of collagen I incubated in the presence of ascorbate ( Figure 2C).…”
Section: Gipie Knockdown Increases Apoptosis and Impairs Cell Prolifementioning
confidence: 99%
“…In the case of procollagen biosynthesis in the ER, these molecular chaperones include BiP (Grp78), Grp94, PDI, P4H and Hsp47 (Chessler and Byers, 1993;Ferreira et al, 1994;Lamande et al, 1995;Wilson et al, 1998;Walmsley et al, 1999;Nagata, 2003). Hsp47 was first identified as a collagen binding protein that resides in the ER and functions as a collagen-specific molecular chaperone (Nagata et al, 1986).…”
Section: Introductionmentioning
confidence: 99%